Perception and utilization of prevention of mother-to-child transmission of human immunodeficiency virus (HIV) services among women living with HIV (2021)
INTRODUCTION: Mother-to-child transmission is the major route of pediatric Human Immunodeficiency Virus (HIV) infection accounting for 90% of childhood HIV infection. Poor utilization of prevention of mother-to-child transmission (PMTCT) of HIV services has been shown in this situation. Hence, the study assessed the perception and utilization of PMTCT services among Women Living with HIV (WLHIV). METHODS: A cross-sectional research design was used with a purposive sampling technique to select 182 WLHIV within reproductive age attending President’s Emergency Plan for Acquired Immunodeficiency Syndrome (AIDS) Relief (PEPFAR)/AIDS Prevention Initiative in Nigeria (APIN) clinic in two secondary Health facilities in Ibadan, Oyo State. A validated structured questionnaire was used for data collection. Descriptive and inferential statistics were used for data analysis. RESULTS: The mean age of the women was 37.0±6.5 years. Majority (74.2%) of the respondents had good knowledge on PMTCT of HIV, positive perception (89%) towards PMTCT services while only 42.9% of the respondents have utilized PMTCT services during pregnancy. However, some of the challenges to use of PMTCT services identified by the respondents were stigma (16.5%), discrimination (15.4%), financial constraint (11.5%) and non-involvement of partner (8.2%). There was a significant association between level of knowledge and PMTCT services utilization (χ2=6.244, p=0.012). CONCLUSIONS: There is need for improvement of knowledge and perception of HIV, MTCT and PMTCT among women through counseling and antenatal education, thereby increasing PMTCT services uptake. Partner involvement, good quality PMTCT services and lack of discrimination of people living with HIV in our society should be encouraged, hence promoting the utilization of PMTCT services.